a study on the characteristics of cotton yarn sized with oxidized starch - ตั้งฐานานุศักดิ์ ยศวัต; เตชธรรมรักข์ ปลื้มจิตต์; นราภิรมย์อนันต์ สมภพ (Frontiers in Engineering Innovation Research, 2009)
The research aims to study the effect of modified tapioca starch on yam and fabric properties in terms of yam and fabric strength, extension at break and abrasion resistance. Fourteen sizing paste recipes were prepared for sizing on 40 Ne cotton yam using the same condition. It was found that cotton yam sized with the recipe of 180 grams modified tapioca starch in a litre of water enhances the property quite similar to cotton yam sized with the typical sizing paste that contain auxiliaries such as polyvinyl alcohol, acrylic and lubricant in the paste. The abrasion resistance of yarn sized with the typical recipe is 1,154.5 revolutions whereas the abrasion resistance of yam sized with S 180 is 1,114.2 revolutions. The two warp yams sized with typical recipe and 5180 were used to prepare sample fabrics. The two fabric samples compose of two different warp yam were tested after desizing. Fabric weight of the two fabric samples using typical sizing recipe and the 5180 recipe are 146.92 g/sq.m. and 146.47 g/sq.m., respectively. Fabric tensile strength at the warp side of the fabric using typical sizing recipe is 243.32 N (at the extension of 15.74 mm) and 221.98 N (at the extension of 16.5 mm) for the other. Abrasion resistance of the two fabrics are 49,000 revolutions and 48.333 revolutions.